Sajjilu Arab American : A Reader in SWANA Studies - Jarmakani, Amira, 1974-; Vinson, Pauline Homsi; Cainkar, Louise (Book collections on Project MUSE., 2021)
"'Sajjulu Arab American' is a carefully curated multi-disciplinary collection of scholarly writings in Arab American studies. Written by both recognized and emerging scholars, the collected essays utilize a wide range of theoretical frames and analytic lenses that are essential to understanding the field"--